Physical Sciences Teachers' Enactment of Simulations in 5E Inquiry-Based Science Teaching - Gloria Makamu; Umesh Ramnarain (MDPI AG, 2022)
The aim of this study was to investigate the pedagogical actions of Physical Sciences teachers when enacting simulations in 5E inquiry-based science teaching for current electricity. Three grade 10 teachers from three high schools who were teaching at schools where ICT resources are available participated in this study. Data was collected by means of lesson observations and interviews. The lesson observation and interview transcripts were coded to generate themes. The results of this study showed that the simulations enable teachers to afford learners with opportunities to engage in hands-on inquiry based on the 5E model. The hands-on activities that students engage in on the simulation help them to explain phenomena from evidence and also allow them to acquire autonomy from the teacher. When students are hands-on, they get the chance to test their hypothesis and also to develop their understanding of the phenomenon that is investigated. Through the use of the simulated activity, teachers were able to support leaners to reflect on activities to reconcile their new knowledge with previous ideas. While it is acknowledged that PhET simulated activity is not a substitute for hands-on practical work in a laboratory, the findings show it can be a powerful tool for supporting inquiry learning.